Peranan Karang Taruna Dalam Meningkatkan Pembangunan Dusun Ngaduman - Krisnawati Setyaningrum N; Renny Aprilliyani; Dyah Palupiningtyas (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
PKM activities were held in Ngaduman Hamlet, Kel. Title, Kec. Getasan, Semarang Regency. This activity involves several stakeholders. The implementation of HR Training activities in Improving the Economy in Ngaduman Hamlet is carried out in four stages, namely the socialization and preparation stage, the implementation stage, and the evaluation stage. In the first stage, internal coordination was carried out by the activity implementing team as well as external coordination involving activity partners. The implementation stage was a coordination process through FGDs in Ngaduman Hamlet which were present and several community communities and also the relevant government, Field Practice Stage through direct field observation, Last stage in the form of activity evaluation, namely technical evaluation and evaluation through direct discussions with several parties to reach conclusions